2017
DOI: 10.1155/2017/7363627
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pressure Pulsation Induced by Rotor-Stator Interaction in Nuclear Reactor Coolant Pump

Abstract: The internal flow of reactor coolant pump (RCP) is much more complex than the flow of a general mixed-flow pump due to high temperature, high pressure, and large flow rate. The pressure pulsation that is induced by rotor-stator interaction (RSI) has significant effects on the performance of pump; therefore, it is necessary to figure out the distribution and propagation characteristics of pressure pulsation in the pump. The study uses CFD method to calculate the behavior of the flow. Results show that the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A range analysis was carried out on the numerical calculation results in Table 10. Range analysis was carried out by Equations (12) and (13), where k i is the average value of j levels of factor i; s is range.…”
Section: The Intuitionistic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A range analysis was carried out on the numerical calculation results in Table 10. Range analysis was carried out by Equations (12) and (13), where k i is the average value of j levels of factor i; s is range.…”
Section: The Intuitionistic Analysismentioning
confidence: 99%
“…Under the rotating stall condition, the blade passing frequency (i.e., three times the rotation frequency) decreased by 50% because of alternate stalled and unstalled passages; when the rotating stall occurred, the amplitude of the pressure fluctuation was much higher than that at unstalled points. Zhang et al [13] studied the pressure pulsation characteristics induced by the rotor-stator interaction in a nuclear reactor coolant pump. At the nominal flow, the flow rate distribution in the guide vanes was relatively uniform, and the amplitude of the pressure pulsation reached the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary flow simulation model of the RCP has been verified by grid independence verification [3] and performance test in our previous researches [19]. During normal operation, the temperature of the liquid in RCP is about 280 • C. Ignoring the influence of trace boric acid [20] and referring to the look-up table, it can be found that the physical property parameters of the liquid are a density of 750 kg/m 3 When the computation stopped, the steady-state static pressure on the impeller boundaries was recorded, which is shown in Figure 4. The static pressure on the outside of the hub is greater than that on the inside.…”
Section: Flow Simulation Of the Rcpmentioning
confidence: 99%
“…The reactor coolant pump (RCP) drives cooling water circulation in the nuclear power plant [1], which brings the heat of the nuclear reactor to the steam generator, thereby producing steam to generate electricity. The RCP impeller rotates at high speed in a high-temperature, high-pressure and strong-radiation environment [2,3]. To ensure the long-term operation of the nuclear power plant, hydraulic resonance should be avoided [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tsukamoto et al [28][29][30] researched the rotor-stator interaction in a diffuser pump with the vortex method and pressure fluctuation measurement, and unsteady hydrodynamic forces excited by the interaction between the impeller and the vaned diffuser with the same number of vanes as impeller were studied as well. Zhang et al [31] used CFD method to study pressure pulsation induced by rotor-stator interaction of a general mixed-flow pump.…”
Section: Introductionmentioning
confidence: 99%